(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The subject of the evolution of fire insurance of the hottest topics accidents, because it falls within the commercial insurance, as its importance is reflected for being a security source and contentment of the insured person and so it is worth pointing out the importance of fire insurance in enterprises and organizations of all kinds, because of the guarantee of its assets from meridian as well as protection from the effects of the fire therefore ensure continuity in the performance of their activities